WOMEN DURING THE SECOND WORLD WAR THEIR SERVICES AND COURAGE IN THE FIELD OF MEDICINE - Mutabar M. Uralova (Galaxy International Interdisciplinary Research Journal, 2021)
In this article is described the work of women in Uzbekistan in the field of medicine during World War II. At the front, the women provided a large amount of military equipment, weapons,medicine, clothing, and food. On the battlefields, they were seriously wounded and wounded soldiers were taken out of the battlefields. They were provided with first aid, treated in military hospitals and camps, and returned to duty on the basis of historical sources and archival materials.